Pengaruh Kualitas dan Desain Produk terhadap Keputusan Pembelian pada Produk Adidas di Perfektur Okayama, Jepang (Studi Kasus pada Mahasiswa dan Pemagang Indonesia) - Muakhor, Abdul Bari Kamal; Savitri, Citra; Suroso, Suroso; Ohnishi, Masahiro (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
In Japan, fashion and sports products are very diverse, from local brands to international brands. Local brands from Japan can also compete with competitors from international brands. Therefore, the researcher intends to do something about one of the most famous international brands, namely Adidas. The independent variable of this research is the influence of product quality and product design on the related variable, namely purchasing decisions. The population of this study were students and apprentices in the Okayama prefecture, Japan who came from Indonesia who had purchased Adidas products, the number of samples taken was 30 respondents. The sample used is purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis used multiple linear regression, partial test analysis using t test and F test (simultaneous). Testing the effect between variables using SPSS (Statistical Product Service Solutions) version 26.00 software. The results of the study according to the t-test (partial) concluded that product quality does not significantly influence purchasing decisions, product design affects purchasing decisions. Based on the results of the F test, it is concluded that product quality and product design have a simultaneous effect on purchasing decisions.